PERSEPSI GURU TERHADAP PENGGUNAAN TEKNOLOGI EDUKASI BERBASIS ARTIFICIAL INTELLIGENCE DI MAS AL WASHLIYAH 12 PERBAUNGAN - Alfi Syahria, Bunga; Darlis, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to understand teachers’ perceptions of the use of Artificial Intelligence (AI)-based educational technology at MAS A1 Washlivah 12 Perbaungan. This study employs a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The subjects of this research consist of teachers who have used or been exposed to AI-based educational applications, such as adaptive learning platforms, chatbots, and student performance analysis systems. The research results show that the majority of teachers have a positive perception of the use of AI in education, especially regarding time efficiency, ease of access to information, and the enhancement of personalized learning. However, some challenges were also found, such as limited understanding of technology, lack of training, and concerns about the reduced role of teachers in the teaching and learning process. Overall, this research recommends the need for continuous training and technology assistance for teachers so that the use of AI in education can be more optimal.